2021
DOI: 10.3390/ijerph18115707
|View full text |Cite
|
Sign up to set email alerts
|

Gender Influences on Physical Activity Awareness of Adolescents and Their Parents

Abstract: The imbalances between the actual physical activity (PA) of adolescents and the subjective perception both they and their parents have in this regard can play an important role in perpetuating inactive lifestyles. The aim of this study is to analyse these discrepancies by considering gender as a conditioning factor. The participants in the study were 1697 adolescents, 1244 mothers and 1052 fathers in the educational communities of 26 secondary schools located in urban environments of the Autonomous Community o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Regarding differences in terms of PA patterns in adolescents with ADHD, the second most important result of this study is that there were significant differences between boys and girls in terms of the achievement of PA recommendations for health and the amount of PA performed at lunchtime. This finding coincides with the existing literature since girls are less active than boys (Béghin et al, 2019; Camacho-Miñano et al, 2011; Kallio et al, 2020; Lago-Ballesteros et al, 2021; Mercurio et al, 2021; Moreno-Llamas et al, 2021; Owen et al, 2017; Rosselli et al, 2020). On the other hand, our data reflects that during lunchtime, 88.9% of girls with ADHD, sat down, stood down, or walked around.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding differences in terms of PA patterns in adolescents with ADHD, the second most important result of this study is that there were significant differences between boys and girls in terms of the achievement of PA recommendations for health and the amount of PA performed at lunchtime. This finding coincides with the existing literature since girls are less active than boys (Béghin et al, 2019; Camacho-Miñano et al, 2011; Kallio et al, 2020; Lago-Ballesteros et al, 2021; Mercurio et al, 2021; Moreno-Llamas et al, 2021; Owen et al, 2017; Rosselli et al, 2020). On the other hand, our data reflects that during lunchtime, 88.9% of girls with ADHD, sat down, stood down, or walked around.…”
Section: Discussionsupporting
confidence: 92%
“…This statement agrees with Cook et al (2015) who claim that youth with ADHD are significantly less likely than their peers to meet recommendations for vigorous PA (3 days per week or month). As mentioned, in terms of gender, according to literature girls are less active than boys (Béghin et al, 2019;Camacho-Miñano et al, 2011;Kallio et al, 2020;Lago-Ballesteros et al, 2021;Mercurio et al, 2021;Moreno-Llamas et al, 2021;Owen et al, 2017;Rosselli et al, 2020). Worryingly, in this sense, MVPA declines by approximately 4.2% to 7% per year between ages 12 and 18 years, and more recent studies indicate that girls' PA levels decline at a greater rate than boys (Borde et al, 2017;Jones et al, 2020;Owen et al, 2017;Pearson et al, 2015;Spencer et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…As described above, traveling includes the non-optional component of 'must arrive somewhere'. Additionally, adolescents seem to be mostly unaware, on how much PA is needed to achieve a healthy lifestyle (Lago-Ballesteros, García-Pascual, González-Valeiro, & Fernández-Villarino, 2021). Thus, if one manages to reach a destination somehow, adolescents might not perceive choosing a passive mode of transport as 'failure' because one still has achieved to arrive at the desired destination.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism observed in the presented study for male adolescents may be also confirmed by the studies of the other authors, as it is stated that athletic adolescents present healthier food habits than non-athletic ones [ 66 , 67 ]. Such difference may be explained by the different roles of physical activity for boys and girls—as boys are in general more physically active than girls [ 68 ] and overestimate their level more than girls [ 69 ], it may be supposed that physical activity may be for them more important and they may present some actions to increase their physical fitness, while for girls only decreasing fitness may motivate them to counteract it.…”
Section: Discussionmentioning
confidence: 99%